THE EFFECT OF PRECIPITATIONS IN A VEGETATION PERIOD ON PRODUCTIVITY OF THE ZONED SPRING BARLEY VARIETIES IN THE ARID CENTRAL ZONE OF THE REPUBLIC OF KALMYKIA - B. А. Goldvarg; М. V. Boktaev; Е. G. Filippov; А. А. Dontsova (Зерновое хозяйство России)
In the arid central zone of the Republic of Kalmykia, one of the limiting factors that affects spring barley productivity is the soil moisture content during a vegetation period. The paper discusses the results of a long-term research of zoned spring barley varieties of various breeding institutions in the experimental field of the KRIA named after M. B. Narmaeva, a branch of the FSBSI “PAFRC RAS” to study the effect of instability of soil moisture in a vegetation period on their productivity and especially in the period of grain filling. Field trials were carried out according to the Methods of State Variety Testing of agricultural crops and Methodology of a field trial. In the course of the studies it was found that in arid years the variety “Shchedry” formed a larger yield than that of other zoned varieties. Moreover, in the wet years of 2016 and 2017 the variety “Shchedry” productivity was inferior to the varieties “Prerii” and “Strannik” on average. It has been revealed that in conditions with uneven precipitation in different years, June precipitation has a decisive effect on spring barley productivity in the central zone of the Republic of Kalmykia.